The effects of physical activity on life satisfaction : a study on Icelandic adolescents - Thelma Björg Magnúsdóttir 1991- (2017)
Well-being and life satisfaction are complex concepts based on subjective evaluation of quality and satisfaction of life. This study was conducted to see if physical activity affects life satisfaction among adolescent. Numerous studies have examined the determinants of well-being. The variables used in this study were consistent with previous researches in this particular field, however, the current study was conducted in Iceland. The hypotheses in this study were two, the first was that physical activity contributes to greater life satisfaction among young people. The second hypothesis was that boys evaluate their life satisfaction generally as better than girls. To answer these hypotheses a detailed questionnaire was sent to all students in upper secondary schools in Iceland. A population-based sample of 3,618 students in tenth grade, 1,783 males, and 1,731 females was used. These numerical data were obtained from an existing international study named Health Behavior in School-aged Children (HBSC), which collects information about welfare, health, social environment and living conditions of adolescents. The results in this study were consistent with prior researches since boys reported higher life satisfaction than girls. Physical activity had a positive impact on life satisfaction of participants regardless of their gender. Keywords: Life satisfaction, health, depression, physical activity and well-being Vellíðan og lífsánægja eru margþætt hugtök byggð á huglægu mati einstaklingsins á eigin gæðum og ánægju með lífið. Eftirfarandi rannsókn var framkvæmd í þeim tilgangi að kanna hvort líkamleg hreyfing hafi jákvæð áhrif á lífsánægju unglinga. Fjölmargar rannsóknir hafa skoðað áhrif lífsánægju. Breytur rannsóknarinnar voru í samræmi við fyrri rannsóknir sem unnar hafa verið á þessu sviði en eftirfarandi rannsókn var framkvæmd á Íslandi. Tilgátur rannsóknarinnar voru tvær, annarsvegar að líkamleg hreyfing hafi jákvæð áhrif á lífsánægju ungmenna og hins vegar að drengir meti lífsánægju sína hærri en stúlkur. Til ...